Cost analysis error? Exploring issues relating to whole-life cost estimation in sustainable housing. Issue 1 (7th April 2014) - Sloan, Brian; Tokede, Olubukola; Wamuziri, Sam; Brown, Andrew
Abstract : Purpose: – The main purpose of the study is to promote consideration of the issues and approaches available for costing sustainable buildings with a view to minimising cost overruns, occasioned by conservative whole-life cost estimates. The paper primarily looks at the impact of adopting continuity in whole-life cost models for zero carbon houses. Design/methodology/approach: – The study embraces a mathematically based risk procedure based on the binomial theorem for analysing the cost implication of the Lighthouse zero-carbon house project. A practical application of the continuous whole-life cost model is developed and results are compared with existing whole-life cost techniques using finite element methods and Monte Carlo analysis. Findings: – With standard whole-life costing, discounted present-value analysis tends to underestimate the cost of a project. Adopting continuity in whole-life cost models presents a clearer picture and profile of the economic realities and decision-choices confronting clients and policy-makers. It also expands the informative scope on the costs of zero-carbon housing projects. Research limitations/implications: – A primary limitation in this work is its focus on just one property type as the unit of analysis. This research is also limited in its consideration of initial and running cost categories only. The capital cost figures for the Lighthouse are indicative rather than definitive. Practical implications: – The continuous whole-life cost technique is a novel and innovative approach in financial appraisal […] Benefits of an improved costing framework will be far-reaching in establishing effective policies aimed at client acceptance and optimally performing supply chain networks. Originality/value: – The continuous whole-life costing pioneers an experimental departure from the stereo-typical discounting mechanism in standard whole-life costing procedures.